The Impact Of Real Earnıng Management On Stock Returns Through Free Cash Flow To The Fırm Empırıcal Study Of Basıc And Chemıcal Industrı Sector Companıes Lısted On The Beı For The Perıod 2018-2022 - Asyad Madani Al Aziz; Rahmawati Rahmawati; Novia Rahma Suryadi; Mada Purwanto Wahyu Nugroho (Cita Konsultindo Research Center, 2024)
The company's financial performance can reflect to investors how the company's management works and operates in generating profits. In this study, the type of data used is quantitative data in the form of annual financial reports of manufacturing companies in the basic and chemical industry sectors on the IDX in 2018 - 2022. This study aims to examine the relationship between Real Earning Management and Stock Return through FCFF. The sampling selected in this study used purposive sampling method and used SPSS version 25. The results showed that the direct effect of the Real Earning Management variable was not statistically significant so that it could be said that the variable had no direct effect on Stock Returns. The indirect effect of FCFF is able to mediate the influence between CFO, COGS, INV, PROOD, and DISEXP on Stock Returns. The indirect effect is formed through the direct effect between the CFO, COGS, INV, PROOD, and DISEXP variables on FCFF and the direct effect between FCFF on Stock Returns. Based on these results, it can be seen that the direct effect of CFO and DISEXP variables is not statistically significant so that it can be said that Real Earning Management has no effect on FCFF which is a measurement of the company's financial performance.